Standard endoscopy with random biopsies versus narrow band imaging targeted biopsies in Barrett's oesophagus: a prospective, international, randomised controlled trial. Issue 1 (7th February 2012) - Sharma, Prateek; Hawes, Robert H; Bansal, Ajay; Gupta, Neil; Curvers, Wouter; Rastogi, Amit; Singh, Mandeep; Hall, Matt; Mathur, Sharad C; Wani, Sachin B; Hoffman, Brenda; Gaddam, Srinivas; et al.
Abstract : Background: White light endoscopy with random biopsies is the standard for detection of intestinal metaplasia (IM) and neoplasia in patients with Barrett's oesophagus (BO). Narrow band imaging (NBI) highlights surface patterns that correlate with IM and neoplasia in BO. Objective: To compare high-definition white light (HD-WLE) and NBI for detection of IM and neoplasia in BO. Design: International, randomised, crossover trial comparing HD-WLE and NBI. Patients referred for BO screening/surveillance at three tertiary referral centres were prospectively enrolled and randomised to HD-WLE or NBI followed by other procedures in 3–8 weeks. During HD-WLE, four quadrant biopsies every 2 cm, together with targeted biopsies of visible lesions (Seattle protocol), were obtained. During NBI examination, mucosal and vascular patterns were noted and targeted biopsies were obtained. All biopsies were read by a single expert gastrointestinal pathologist in a blinded fashion. Results: 123 patients with BO (mean age 61; 93% male; 97% Caucasian) with mean circumferential and maximal extents of 1.8 and 3.6 cm, respectively, were enrolled. Both HD-WLE and NBI detected 104/113 (92%) patients with IM, but NBI required fewer biopsies per patient (3.6 vs 7.6, p<0.0001). NBI detected a higher proportion of areas with dysplasia (30% vs 21%, p=0.01). During examination with NBI, all areas of high-grade dysplasia and cancer had an irregular mucosal or vascular pattern. Conclusions: NBI targeted biopsies can have the same IM detection rate as an HD-WLE examination with the Seattle protocol while requiring fewer biopsies. In addition, NBI targeted biopsies can detect more areas with dysplasia. Regular appearing NBI surface patterns did not harbour high-grade dysplasia/cancer, suggesting that biopsies could be avoided in these areas.